Characterization of Metabolites in the Biotransformation of 2,4,6-Trinitrotoluene with Anaerobic Sludge: Role of Triaminotoluene - Hawari, Jalal (American Society for Microbiology, 1998)
The present study describes the biotransformation of 2,4,6-trinitrotoluene (TNT) (220 μM) by using anaerobic sludge (10%, vol/vol) supplemented with molasses (3.3 g/liter). Despite the disappearance of TNT in less than 15 h, roughly 0.1% of TNT was attributed to mineralization ((14)CO(2)). A combination of solid-phase microextraction–gas chromatography-mass spectrometry and liquid chromatography-mass spectrometry identified two distinctive cycles in the degradation of TNT. One cycle was responsible for the stepwise reduction of TNT to eventually produce triaminotoluene (TAT) in relatively high yield (160 μM). The other cycle involved TAT and was responsible for the production of azo derivatives, e.g., 2,2′,4,4′-tetraamino-6,6′-azotoluene (2,2′,4,4′-TA-6,6′-azoT) and 2,2′,6,6′-tetraamino-4,4′-azotoluene (2,2′,6,6′-TA-4,4′-azoT) at pH 7.2. These azo compounds were also detected when TAT was treated with the anaerobic sludge but not with an autoclaved sludge, suggesting the biotic nature of their formation. When the anaerobic conditions in the TAT-containing culture medium were removed by aeration and/or acidification (pH 3), the corresponding phenolic compounds, e.g., hydroxy-diaminotoluenes and dihydroxy-aminotoluenes, were observed at room temperature. Trihydroxytoluene was detected only after heating TAT in water at 100°C. When (13)CH(3)-labeled TNT was used as the N source in the above microcosms, we were unable to detect (13)C-labeled p-cresol or [(13)CH(3)]toluene, indicating the absence of denitration or deamination in the biodegradation process. The formation and disappearance of TAT were not accompanied by mineralization, suggesting that TAT acted as a dead-end metabolite.